Inflammatory stimuli alter bone marrow composition and compromise bone health in the malnourished host - Osorio, E. Yaneth; Gugala, Zbigniew; Patterson, Grace T.; Palacios, Genesis; Cordova, Erika; Uscanga-Palomeque, Ashanti; Travi, Bruno L.; Melby, Peter C. (Frontiers in Immunology, 2022)
Inflammation is a significant contributor to the pathogenesis of childhood malnutrition. We investigated the effect of malnutrition and inflammatory challenge on bone marrow composition and bone health. We studied an established murine model of moderate acute malnutrition at baseline and after acute inflammatory challenge with bacterial lipopolysaccharide (LPS), a surrogate of Gram-negative bacterial sepsis, or Leishmania donovani, the cause of visceral leishmaniasis. Both of these infections cause significant morbidity and mortality in malnourished children. Of the 2 stimuli, LPS caused more pronounced bone marrow changes that were amplified in malnourished mice. LPS challenge led to increased inflammatory cytokine expression (IL-1b, IL-6, and TNF), inflammasome activation, and inflammatory monocyte accumulation in the bone marrow of malnourished mice. Inflammatory challenge also led to increased expansion of mesenchymal stem cells (MSCs), bone marrow adiposity, and expression of genes (Pparg, Adipoq, and Srbp1) associated with adipogenesis in malnourished mice. This suggests that inflammatory challenge promotes differentiation of BM MSCs toward the adipocyte lineage rather than toward bone-forming osteoblasts in the malnourished host. Concurrent with this reduced osteoblastic potential there was an increase in bone-resorbing osteoclasts, enhanced osteoclast activity, and upregulation of genes involved in osteoclastogenesis. Lastly, we evaluated the effect of replacing lipid rich in omega-6 fatty acids (corn oil) with lipid rich in omega-3 fatty acids (fish oil) in the nutrient-deficient diet. LPS-challenged malnourished mice that received dietary fish oil showed decreased expression of inflammatory cytokines and Rankl and reduced osteoclast differentiation and activation in the bone marrow. This work demonstrates that the negative effect of inflammatory challenge on bone marrow is amplified in the malnourished host. Increasing dietary intake of omega-3 fatty acids may be a means to reduce inflammation and improve bone health in malnourished children.